Internal Displacements Due to Climate Change & Natural Disasters In Pakistan: Review & Implementation of UN Guiding Principles for IDPs & their legal status and rights in Pakistan - Muhammad Bin Inam; Dr Rizwana Gul (Dialogue Social Science Review (DSSR), 2025)
The displacements caused by climate change and natural disasters are a pressing issue in Pakistan. Over the years, millions of people have directly been affected by natural disasters which are often caused by climate change., the same number of millions of Pakistanis are also indirectly affected by the destruction from natural disasters, as evident from the food shortages, infrastructure damage, loss of business, and inflation. This paper investigates the specific legal and human rights hurdles that these communities face in displaced communities. By scrutinizing existing legal frameworks in Pakistan seen through the United Nations (UN) Guiding Principles for Internally Displaced People (IDP's), this paper aims to offer insights that can inform practical policy recommendations, thus strengthening the legal infrastructure to protect legal rights of environmentally induced IDPs in Pakistan.